RANCANGAN ALAT PEMBATASAN PENGGUNAAN HANDPHONE PADA PENGEMUDI BUS BERBASIS INTERNET OF THINGS - Prasetyo, Ilham Bagus; Pratindy, Raka; Srianto (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2023)
The phenomenon of bus drivers still using mobile phones while driving is still prevalent today. This happens because bus drivers have the opportunity to reach for their mobile phones while driving, making it necessary to restrict the use of mobile phones by bus drivers. This research aims to develop an Internet of Things (IoT)-based device that can monitor the use of mobile phones by bus drivers while driving. Using the Research and Development method, this study resulted in a design for a device that restricts the use of mobile phones by bus drivers. This device detects the installation of a mobile phone, ownership of the mobile phone, and the vehicle's speed. Through the data input and data processing in the device's design, it produces warnings in the form of text and sound, as well as violation reports sent to the bus company supervisor. This helps the bus company in monitoring bus drivers. This device's design can serve as a reference for the development of a device that can be implemented in buses to restrict the use of mobile phones while driving. ABSTRAK Fenomena pengemudi bus mengemudi sambil mengoperasikan handphone masih dijumpai hingga saat ini. Hal tersebut terjadi karena pengemudi bus memiliki kesempatan untuk menjangkau handphone pada saat mengemudi, sehingga diperlukan upaya pembatasan kesempatan penggunaan handphone pada pengemudi bus. Penyusunan karya ilmiah ini menggunakan metode penelitian Research & Development (R&D). Penelitian ini menghasilkan sebuah rancangan alat pembatasan penggunaan handphone pada pengemudi bus berbasis Internet of Things (IoT). Alat ini mendeteksi pemasangan handphone, kepemilikan handphone, dan kecepatan kendaraan. Output yang dihasilkan yaitu berupa peringatan dalam bentuk tulisan dan suara serta laporan pelanggaran yang dikirimkan kepada pengawas perusahaan otobus. Rancangan alat ini bertujuan untuk meminimalisir kesempatan pengemudi untuk dapat menjangkau handphone pada saat mengemudi. Selain itu, alat ini juga dapat membantu perusahaan otobus dalam melakukan pengawasan terhadap pengemudi bus.